Analisis Historis Pendidikan Islam pada Masyarakat Madinah - Ainusyamsi, Fadlil Yani (TAJDID, 2019)
This article aims to discover the history of education in the early of Islam in Medina. This research uses a historical analysis method. Research data sources are a number of literatures that is considered valid and credible. This research succeeded in describing several findings. Education pattern of Muhammad in plurality of Medina society tended to be informal, emphasizing the role of family and halâqahs. This study also found historical facts that the values ​​of pluralism, intellectualism, and the spirit of urbanism had become a part of learning and education of Muhammad. The style of the leadership of the Muhammad in the midst of the pluralist society of Medina offers a pattern that is very concerned about the existence of the community students through an example (uswah and qudwah hasanah). In addition, the Prophet taught with full attention and tenderness and humility. He never underestimated someone who came asking for teaching. Islamic education pattern of Muhammad in Medina was marked by a number of characteristics, namely education organized by through the construction of the mosque as a centre of movement, centre of education, and centre of community. The principle carried out by the Muhammad in fostering society is the ethical approach (moral virtue). He believes that moral values ​​not only create peace between individuals in a nation, but also between nations